Visualizing Belief and Piety in Iranian Shi‘ism: By Ingvild Flaskerud (New York: Continuum, 2010. hbk. 306 pages.) (American Journal of Islam and Society, 2011)
In her book, Ingvild Flaskerud once and for all dispels the idea that Islamlacks and opposes all forms of visual art. Hers is a pioneering work, whichguides her readers through Twelver Shi‘i visual culture in Iran. She framesher discussion by drawing on semiotic theory, particularly Charles SandersPeirce and Roland Barthes, in order to show both the interpretive possibilitiesinherent in visual piety and the ways in which meaning is fixed.Flaskerud is uniquely positioned for writing about visual piety, as she hasalready produced an artistic visual film (“Standard Bearers of Hussein:Women Commemorating Karbala,” 2003) on Shi‘i women’s practices inIran. Visualizing Belief and Piety in Iranian Shi‘ism is a Geertzian “thick description”(Geertz, The Interpretation of Cultures) composed of three parts,each of which is followed by black-and-white pictures analyzed in thatpart. The first two parts address two iconographic themes respectively. Thethird discusses the usage of pious art in votive practices and ritual spaces ...